The Northmen in Britain - Hull, Eleanor, 1860-1935; Williams, Morris Meredith, 1881-1973 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Northmen in Britain" by Eleanor Hull is a historical account written in the early 20th century. The book delves into the Viking Age and its significant impact on Britain, detailing the Norsemen's invasions, settlements, and the cultural interactions that ensued during the 9th to 11th centuries. It presents a well-researched narrative about how these seafaring warriors shaped British history and society, particularly through their conquests and the establishment of kingdoms. The opening of the work sets the stage for the arrival of the Northmen, highlighting the initial Viking raids on Britain's shores beginning around 787 AD and the resulting fear and violence among the local populations. Hull references historical accounts and Norse sagas to outline the significance of the Viking presence, illustrating the Norsemen's transition from mere raiders to settlers who established lasting kingdoms in Northumbria and beyond. The narrative provides insights into their social structures, conflicts, and interactions with the native inhabitants, setting the foundation for the detailed exploration of notable figures and events that will follow in the subsequent chapters. (This is an automatically generated summary.)
Release date is 2022-10-11
MWS, Charlie Howard, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Northmen -- Great Britain; Great Britain -- Civilization -- Scandinavian influences; Great Britain -- History -- To 1066